PENGUATAN FOKUS BELAJAR SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN VARIATIF BERBASIS KETERLIBATAN EMOSIONAL - Ahmad Akbar; Alhamdu; Darul Rizwan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2026)
Abstract: This article discusses the importance of strengthening elementary school students' learning focus through varied, emotional engagement-based learning. Learning focus is a critical factor influencing students' success in understanding material and achieving optimal learning outcomes. Varied learning that engages students' emotional aspects is expected to create an enjoyable learning atmosphere, thereby increasing concentration and learning motivation. This article was prepared using a literature review method by examining a number of relevant national and international journal articles published between 2021 and 2025. The results show that varied learning strategies, such as educational games, visual and audio media, collaborative learning, ice breaking, positive teacher-student relationships, and learning differentiation, consistently contribute to increased focus, motivation, and emotional engagement among students. The implication is that teachers need to implement varied, enjoyable learning strategies that consider students' emotional conditions so that the learning process in elementary schools can run more optimally. Keyword: learning focus, varied, emotional, elementary